un Modelo de Evaluación Psicojurídico Basado en Tecnologia Computacional, de la Alienación Parental en Niños Niñas y Adolescentes Colombianos : Modelo de Evaluación Psicojurídico Basado en Tecnologia Computacional - Ortiz Bastidas, Jaro Mauricio (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2022)
The present study Model of Psycho-legal Evaluation Based on Computational Technology, of Parental Alienation in Colombian Children and Adolescents is carried out in order to determine a predictive model in the evaluation of AP Parental Alienation in children and adolescents over 9 years of age. to generate an algorithm of Artificial Neural Networks RNA, to be implemented by the psychosocial teams of the different government entities that help in making psycho-legal decisions when determining intrafamily violence, Parental Alienation AP and the choice of parents suitable for custody and care of their minor children. An experimental study will be carried out, which seeks to determine associated variables and predictors of PA in which alienating behaviors and alienating behaviors are found, relating them to the prosodic element of communication, which will allow the integration of psycho-legal variables with other linguistic physical magnitudes. . The sample will correspond to 50 Colombian boys, girls and adolescents, ages ranging from 9 to 15 years, who voluntarily agree to participate in the project as well as their parents. The instruments to be used will be a semi-structured interview with minors and parents in the study that takes into account variables that make up the AP (Alienating Behaviors CA_1 Emotional Capture or Kidnapping) and (Alienated Behaviors CA_2 {Avoidance, Contempt, and Irrational Overinvolvement}) , together with the parental alienation instrument ZICAP II.